Cardiovascular Protective Effects of Oral Hypoxia Inducible Factor Prolyl Hydroxylase Inhibitor Roxadustat in the Treatment of Type 4 Cardiorenal-Anemia Syndrome: Protocol of a Randomized Controlled Trial - Wen, Yumin; Xu, Yang; Tian, Hui; Jiang, Sizhu; Jiang, Guofang; Li, Puqing (Frontiers in Medicine, 2022)
Background： Patients with chronic kidney disease (CKD) are at high risk of developing heart failure and anemia, which is defined as type 4 cardiorenal-anemia syndrome (CRAS). CRAS aggravates the deterioration of both kidney and heart function, ultimately results in a high mortality. This study aims at examining the efficacy and safety of roxadustat in the treatment of type 4 CRAS. Methods/design： This study is designed as a randomized, open-label, controlled trial. A total of 68 patients diagnosed with type 4 CRAS will be randomly divided into roxadustat group and erythropoietin with a 1:1 ratio. Participants in the roxadustat group will receive roxadustat with an initial dose of 70mg or 100mg three times a week, and participants in the erythropoietin group will receive subcutaneous injection of erythropietin for 24 weeks, to maintain a hemoglobin ranging from 100 to 120 g per liter. The primary outcome is the change in the heart function, including brain natriuretic peptide (BNP), 6-minutes walk test (6-WT) and left ventricular ejection fraction (LVEF). Secondary outcomes to be assessed include death, cardiovascular events, hospitalization regarding heart failure, Minnesota Heart Failure Quality of life scale (MLHFQ) score, New York Heart Association (NYHA) cardiac function grade, echocardiographic parameters including left ventricular diastolic diameter and volume (LVDD and LVDV) and ventricular mass (LVM), anemia related parameters, inflammatory parameters and safety assessments. Conclusion： The finding of this study will provide potential evidence for roxadustat in CRAS management. Trial registration: Chinese Clinical Trial Registry, ID:ChiCTR2100050031. Registered on 16 August 2021.